Far-Right Extremism, Elections and Hate Crime: a Temporal Evaluation of Bias-Motivated Violence in Slovakia - Whittington, Whitney (The British journal of criminology, 2025)
The present study provides an initial attempt to assess the impact of extremist right electoral support on racially motivated and extremist violent crime rates across Slovak regions. We transcend previous research by examining associations between national and regional elections, immigration rates, vote-shares, and violent hate crime rates utilizing temporal statistics on racially motivated and extremist violent crimes, which are linked with data on support for nationalist parties and on indicators of socio-economic development. Results illustrate that extreme right parties matter, such that the higher their electoral vote-shares, the higher the violent hate crime incidence and victimization rates. We, also, find that high immigration rates strengthen the effect of electoral vote-shares on bias crime in Slovakia.